PENGARUH BRAND EQUITY, KUALITAS PRODUK, DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN BAJU MEREK ERIGO - Pratama, Sendy Tya (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to determine the effect of brand equity, product quality, and lifestyle either partially or simultaneously on purchasing decisions for Erigo brand clothing. This research uses a quantitative approach and is a causal research. The population in this study are all consumers of Erigo products whose number is unlimited or uncountable. The sample was determined as many as 40 students who were taken using an accidental sampling technique. Data collection techniques using questionnaires and data analysis used in this study is multiple linear regression analysis. The results showed that brand equity, product quality and lifestyle had a significant effect on purchasing decisions, while simultaneously brand equity, product quality, and lifestyle had a significant effect on purchasing decisions for Erigo brand clothing.